PENGARUH STRATEGI PEMBELAJARAN MIND MAPPING TERHADAP HASIL BELAJAR SISWA PADA SUB MATERI BRYOPHYTA - Gustia, Arviditya Putri; Hardigaluh, Basuki; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study was purposed to see the influence of mind mapping learning strategy towards students' learning outcomes on the sub material of Briophyte in 10th grade Taruna Bumi Khatulistiwa Senior High School. The Quasi Experiment Design with Nonequivalent control group design was used. The sample of this study was 10th grade science 1 (Experiment class) and 10th grade science 2 (control class). The sample selection technique in this study using the saturation sampling technique in which all members of the population used as sample. The instrument used in this study was 20 questions of multiple choice test. The average of students' learning outcomes who taught using mind mapping learning strategy was 18.64 higher compared to the average of student learning outcomes who taught using conventional learning was 13.82. Based on the U Mann Whitney test, obtained Zcount < Ztable (-6.83 < -1.96), means there was a significant difference between the learning outcomes of students who taught using Mind Mapping learning strategy and conventional. The obtained effect size value was 4.63 which means that the influence of mind mapping learning strategy in learning outcomes was high and contributes > 50%. Â Keywords : Mind Mapping, Learning Strategy, Sub Material of Bryophyte